Accurate lung volume measurements in vitro using a novel inert gas washout method suitable for infants. Issue 5 (1st December 2015) - Shawcross, Anna; Murray, Clare S.; Goddard, Nicholas; Gupta, Ruchi; Watson, Stuart; Horsley, Alexander
Summary: Background: Multiple breath washout (MBW) in infants presents a number of technical challenges. Conventional MBW is based on simultaneous measurement of flow and gas concentrations. These two signals are aligned and combined to derive expired gas volumes from which lung volumes and measures of ventilation inhomogeneity are calculated. Accuracy of measurement becomes increasingly vulnerable to errors in gas signal alignment at fast respiratory rates. In this paper we describe an alternative method of performing MBW in infants. Expired gas is collected and analyzed to derive functional residual capacity (FRC) and lung clearance index (LCI). This eliminates the need for simultaneous measurement of flow, and integration of flow and gas signals, and significantly reduces deadspace. Methods: A highly accurate lung model incorporating BTPS conditions was used to generate realistic infant breathing parameters: FRC of 100–250 mls with respiratory rate of 20–60 min −1 . In vitro accuracy of FRC measurement using the novel MBW method was assessed using the model. Results: Overall mean error (standard deviation) of FRC measurement was −1.0 (3.3)% with 90% of tests falling within ±5%. Discussion: FRC measurement using the novel method has superior accuracy in vitro than previously described systems. By uncoupling the measurement of gas volumes from real‐time flow and gas measurement, this system offers an alternative method of MBW which is well suited to infants.Pediatr Pulmonol. 2016;51:491–497 . © 2015 Wiley Periodicals, Inc.